Green synthesis of graphene-silver nanocomposites and its application as a potent marine antifouling agent - Yee, M.S.L.; Khiew, P.S.; Chiu, W.S.; Tan, Y.F.; Kok, Y.Y.; Leong, C.O. (Elsevier, 2016)
Fouling of marine surfaces has been a perpetual problem ever since the days of the early sailors. The tenacious attachment of seaweed and invertebrates to man-made surfaces, notably on ship hulls, has incurred undesirable economic losses. Graphene receives great attention in the materials world for its unique combination of physical and chemical properties. Herein, we present a novel 2-step synthesis method of graphene-silver nanocomposites which bypasses the formation of graphene oxide (GO), and produces silver nanoparticles supported on graphene sheets through a mild hydrothermal reduction process. The graphene-Ag (GAg) nanocomposite combines the antimicrobial property of silver nanoparticles and the unique structure of graphene as a support material, with potent marine antifouling properties. The GAg nanocomposite was composed of micron-scaled graphene flakes with clusters of silver nanoparticles. The silver nanoparticles were estimated to be between 72 and 86 nm (SEM observations) while the crystallite size of the silver nanoparticles (AgNPs) was estimated between 1 and 5 nm. The nanocomposite also exhibited the SERS effect. GAg was able to inhibit Halomonas pacifica, a model biofilm-causing microbe, from forming biofilms with as little as 1.3 wt.% loading of Ag. All GAg samples displayed significant biofilm inhibition property, with the sample recording the highest Ag loading (4.9 wt.% Ag) associated with a biofilm inhibition of 99.6%. Moreover, GAg displayed antiproliferative effects on marine microalgae, Dunaliella tertiolecta and Isochrysis sp. and inhibited the growth of the organisms by more than 80% after 96 h. The marine antifouling properties of GAg were a synergy of the biocidal AgNPs anchored on the stable yet flexible graphene sheets, providing maximum active contact surface areas to the target organisms.